Product improvement of file compartment / Mohd Faizul Ahmad Nawawi - Ahmad Nawawi, Mohd Faizul (2006)
This project is about study to improve the design of file This project is using CAD programming. The CAD programming that 1 used is SOLID WORK. This programming is more easily too used especially in industrial design. End of this project it is observed symmetry design is more suitable to design and people like than unsymmetrical design.